The revised three-step detour pathway in dolichol biosynthesis is evolutionarily conserved in budding yeast - Kazuki Hanaoka; Kuya Matsunaga; Souichirou Shimizu; Soshi Sakai; Harald Pichler; Kouichi Funato (Proceedings of the National Academy of Sciences, 2026)
The identification of SRD5A3 , a causative gene for congenital disorders of glycosylation (CDGs), together with its yeast ortholog DFG10 , established the prevailing model that dolichol is synthesized from polyprenol in a single step. Subsequently, a recent discovery of DHRSX in CDG patients revised this view and led to the proposal of a three-step detour pathway for dolichol biosynthesis. However, it remains unclear whether this pathway represents a conserved mechanism or reflects evolutionary diversity in eukaryotes. Here, we identified TDA5 as a yeast ortholog of DHRSX . Deletion of TDA5 caused glycosylation defects, reduced dolichol levels, and accumulated polyprenol. All these phenotypes were rescued by expression of DHRSX , but not by DFG10 or SRD5A3 . These findings show that Tda5 serves the same function as DHRSX in yeast, thereby demonstrating conservation of the three-step detour pathway in yeast and supporting a broader eukaryotic framework for dolichol biosynthesis.